In the eye of the storm - Persakis, Antonios (Economic and business review, 2025)
Background and objective: We investigate whether financial reporting quality is associated with economic policy uncertainty and examine the moderating roles of investor sentiment and audit quality during periods of high uncertainty. Methods: This study focuses on firms listed on the Korea Stock Exchange over the period 1998–2021. We employ a dynamic panel-data model and utilize the Arellano–Bover/Blundell–Bond system estimator, a two-step generalized method of moments estimator that leverages instrumental variables to mitigate the issue of endogeneity. Results: The empirical result provides support for the hypothesis suggesting that Korean economic policy uncertainty is positively associated with financial reporting quality, indicating that managers have an incentive to reduce earnings management when economic policy uncertainty increases. In addition, the statistical analyses indicate that financial reporting quality is higher during periods of low investor sentiment, suggesting that managers have incentives to provide high-quality financial reporting when investors are in a bearish sentiment so as to reverse this pessimistic mood. Conclusion: This research may have implications for regulatory authorities and financial market participants who are working on improving financial reporting quality in their countries during periods of high uncertainty. Contribution: The major contribution of our research is its exploration of how economic policy uncertainty in South Korea influences financial reporting quality, revealing that increased uncertainty motivates firms to enhance disclosure practices for greater transparency and information accuracy, especially in contexts of bearish investor sentiment and high audit quality.
Keywords: auditing; economic policy; ekonomska politika; investicije; investments; revizija